2005
DOI: 10.1177/0091270004272732
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Multiple‐Dose Dexloxiglumide on the Pharmacokinetics of Oral Contraceptives in Healthy Women

Abstract: This study was undertaken to evaluate the effect of dexloxiglumide, a selective cholecystokinin receptor antagonist, on the pharmacokinetics of a combination oral contraceptive (OC). A single-blind, placebo-controlled, 2-period crossover study was conducted in 24 healthy young female subjects who received Ortho Tri-Cyclen containing ethinyl estradiol (EE, 0.035 mg) and norgestimate (NE, 0.180 mg/0.215 mg/0.250 mg per 7-day phase, respectively) for 5 days (days 17-21) concurrently with either 200 mg dexloxiglum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…The reaction phenotyping results clearly indicate a dominant role for CYP3A4-mediated metabolism of NGMN (f m of 0.57) with a lesser role for CYP2B6, even lesser role for CYP2C9, and no role for CYP3A5. The implication of CYP3A4 in the metabolism of NGMN is consistent with numerous clinical trials, wherein it was found that daclatasvir, alitretinoin, rosuvastatin, rifaximin, laropiprant, sofosbuvir, ledipasvir, dolutegravir, dexloxiglumide, tenofovir disoproxil fumarate (a prodrug of tenofovir), saxaglipitin, and raltegravir did not influence the exposures of NGMN (Simonson et al, 2004;Roy et al, 2005;Fig. 4.…”
Section: Discussionsupporting
confidence: 80%
“…The reaction phenotyping results clearly indicate a dominant role for CYP3A4-mediated metabolism of NGMN (f m of 0.57) with a lesser role for CYP2B6, even lesser role for CYP2C9, and no role for CYP3A5. The implication of CYP3A4 in the metabolism of NGMN is consistent with numerous clinical trials, wherein it was found that daclatasvir, alitretinoin, rosuvastatin, rifaximin, laropiprant, sofosbuvir, ledipasvir, dolutegravir, dexloxiglumide, tenofovir disoproxil fumarate (a prodrug of tenofovir), saxaglipitin, and raltegravir did not influence the exposures of NGMN (Simonson et al, 2004;Roy et al, 2005;Fig. 4.…”
Section: Discussionsupporting
confidence: 80%
“…Previous data suggest that oral contraceptive concentrations will not demonstrate wide variability within a cycle. 15-17 Therefore, we also evaluated whether there was a period effect—that is, whether DTG administration in the first part of the cycle had a different effect on NGMN and EE compared with administration in the latter part of the cycle. The results of this analysis demonstrated that the order in which DTG or placebo treatment was given had no effect on concentrations of NGMN and EE.…”
Section: Discussionmentioning
confidence: 99%
“…Ethinyl estradiol is metabolized by CYP3A, and drugs that affect CYP3A metabolism can lead to loss of ethinyl estradiol effectiveness. 40 Tipranavir/ritonavir decreases the AUC and C max of ethinyl estradiol by 50%, but does not significantly alter the pharmacokinetics of norethindrone. 20 Therefore, when estrogen-based oral contraceptives are coadministered with tipranavir/ritonavir, alternative or additional contraceptive measures are required, and patients should be monitored for signs of estrogen deficiency.…”
Section: Oral Contraceptives and Estrogensmentioning
confidence: 94%
“…Ethinyl estradiol is metabolized by CYP3A, and drugs that affect CYP3A metabolism can lead to loss of ethinyl estradiol effectiveness 40 . Tipranavir/ritonavir decreases the AUC and C max of ethinyl estradiol by 50%, but does not significantly alter the pharmacokinetics of norethindrone 20 .…”
Section: Considerations For Concomitant Use With Other Drugsmentioning
confidence: 99%